Hubungan Pelaksanaan Tugas Kepala Sekolah dengan Disiplin Kerja Guru di SMK N 3 Pariaman - Adilla Tussa'adah; Sufyarma Sufyarma; Anisah Anisah; Yulianto Santoso (Universitas Negeri Padang, 2021)
This search own to receive explanation on managerial competence and teacher work discipline as well as the relationship between principal managerial competence and teacher work discipline at SMK N 3 Pariaman as seen from developing schools and upgrading the level of school in aspect teaching personnel (variable X) and regarding timeliness teachers at work, adherence to school regulations, and teacher responsibilities at work (variable Y). The population of teachers at SMK N 3 Pariaman in 81 people with a sample of 46 people using the Slovin. The instrument in this study used a likert scale questionare through validity and reliability tests. This data uses product moment correlation with r count 0,297 > r table 0,291 and t count 2,06 > t table 2,00. The result of the research is that there is a relationship between principal managerial competence and work discipline teachers at SMK N 3 Pariaman.